TLR4Polymorphism, Nasopharyngeal Bacterial Colonization, and the Development of Childhood Asthma: A Prospective Birth-Cohort Study in Finnish Children - Johanna T. Teräsjärvi; Laura Toivonen; Juho Vuononvirta; Jussi Mertsola; Ville Peltola; Qiushui He (MDPI, 2022)
We aimed to explore the role of TLR4 (rs4986790) polymorphism in the nasopharyngeal (NP) bacterial colonization and its consequent impact on the development of childhood asthma. A semi-quantitative culture of NP swabs was performed on 473 children at 2 months of age and on 213 children at 13 months of age.TLR4polymorphism was analyzed for 396 children. Children were followed from birth to the age of 7.5 years and the final outcome was physician-diagnosed asthma. The associations betweenTLR4genotype, bacterial colonization, and asthma were analyzed. Children with TLR4 AG or GG genotype were more often colonized withMoraxella catarrhalisat 2 months of age (p= 0.009) andHaemophilus influenzaeat 13 months of age (p= 0.018). Children who were colonized withH. influenzaeat 13 months of age had a significantly higher risk of later development of asthma (p= 0.004).M. catarrhalisorH. Influenzaecolonization at 2 months of age orTLR4genotype Asp299Gly were not associated with the development of childhood asthma.TLR4Asp299Gly polymorphism was associated with an increased risk of colonization ofM. catarrhalisandH. influenzaein children. The colonization withH. influenzaeat 13 months of age was associated with a higher risk of later development of childhood asthma.